Using social media as e-Portfolios to support learning in higher education: a literature analysis - Chang, Siew Lee; Muhammad Kamarul Kabilan (Springer New York LLC, 2022)
Although e-Portfolio is acknowledged as one of the powerful pedagogical practices that enhance learning in higher education (HE), not much is known about the types of social media (SM) utilized as e-Portfolios and the benefits for students. This literature analysis, using directed content analysis, aims to explore the above vacuum. The research questions in this study are: (1) In what ways do the SM as e-Portfolios benefit students in HE? (2) To what extent are the benefits of SM as e-Portfolios comparable to those of conventional e-Portfolios? and (3) What are the drawbacks that practitioners and researchers need to be concerned with? Findings indicate that blogs are the most popular SM used as e-Portfolios to support learning, followed by social networking sites and collaborative projects. The study yields 13 advantages and 12 drawbacks when SM is manipulated as e-Portfolios. These findings conclude that the use of SM as e-Portfolios has a great potential in supporting students’ learning and development by providing an environment for them to learn meaningfully from their experiences and engage in critical reflections and dialogues that allow them to gain new knowledge and valuable insights and thus, improve their skills. A pedagogical framework for the planning and implementation of SM as e-Portfolios is suggested based on the findings and aims of the papers that were reviewed.